Contribution To Food Commodity Prices Against Inflation In Kupang City - Khristina Kiha, Emilia; Timo, Fredirikus (STMIK Dharma Wacana, 2024)
The aim of this research is to find out how food commodity prices influence inflation in the short and long term in Kupang City and the influence of previous inflation on inflation in Kupang City. The data used in this research is time series data in the form of monthly data on the prices of food commodities such as rice, red chilies, shallots, chicken eggs and chicken meat as well as monthly data on inflation in Kupang City. The research method used is the Partial Adjustment Model (PAM). The research results show that (1) Rice prices have a negative and insignificant effect on inflation in the short and long term (2) Red chili prices have a positive and significant effect on inflation in the short and long term. (3) The price of shallots has a positive and insignificant effect on inflation in Kupang City in the short and long term. (4) The price of chicken eggs has a negative and insignificant effect on inflation in Kupang City (5) The price of chicken meat has a positive and insignificant effect on inflation in Kupang City (6) Previous inflation had a negative and insignificant effect on inflation in Kupang City